Ketahanan Varietas dan Aksesi Padi terhadap Virus Kerdil - Roza, Celvia; Suprihanto, Suprihanto; Kusdiaman, Dede; Widiarta, I Nyoman; Nuryanto, Bambang; Rumasa, Oco (Jurnal Fitopatologi Indonesia, 2021)
Resistance of Rice Varieties and Accessions to Dwarf Viruses Resistance identification of rice germplasm was conducted to obtain information on resistant response of varieties and accessions to rice dwarf virus, i.e. Rice ragged stunt virus (RRSV) and Rice grassy stunt virus (RGSV). The research was carried out at the greenhouse of the Indonesian Center for Rice Research in MT1/MT2 in 2018. The genetic material tested involved 19 rice varieties that had been released and 50 rice accessions from germplasm collection of the Indonesian Center for Rice Research, IAARD, Ministry of Agriculture. Disease observations followed the 2014 IRRI SES scoring method. Response of the test plants to RRSV could be grouped into susceptible (1 variety and 22 accessions), moderately resistant (18 varieties and 22 accessions), and resistant 2 accessions, i.e. MDK Karawang (800 grains/malai) (10597), and Pulo Hitam (10615). Responses of test plants to RGSV can be grouped into susceptible (16 varieties and 34 accessions), moderately resistant (3 varieties and 11 accessions), and resistant (1 accession, i.e. Ketik 1-1062). Furthermore, RRSV and/or RGSV resistant rice accessions can be used as genetic material to breed new varieties resistant to dwarf viruses.